Effect of non-genetic factors on linear type traits score in Sahiwal cattle - Devi, Indu; Kumar, Ajay; Lathwal, Surender Singh; Tomar, Divyanshu Singh; Singh, Pawan; Mamta; Singh, Yajuvendra (Indian Journal of Dairy Science, 2024)
The goal of the present investigation was to determine if environmental or non-genetic variables may affect linear type scores in Sahiwal cows. For this purpose, 246 observations were obtained from 23 linear type traits on 150 Sahiwal cattle from 2019 through 2021. Data was analyzed by the least square technique to examine the effect of non-genetic factors on conformation traits. All the data were analyzed by using univariate analysis of variance in the GLM of SPSS. In this study, the season had no statistically significant impact on linear type traits. Parity had a significant (p<0.05) effect on chest width, body depth, rump width, fore udder attachment, udder depth, rear udder width, central ligament, fore teat length and rear teat length. Stage of lactation had a significant (p<0.05) effect on body depth, body condition score, rear udder height and rear udder width. According to the study’s findings, the parity, and lactation stages were significant drivers of variance for most features of the linear type. To minimize known animal differences and achieve accurate estimates of the attributes, data must be adjusted for these effects.